Plasma sputtered platinum saturable absorber with variable sputtering time for Q-switched erbium-doped fiber laser. (April 2021) - Yuzaile, Y.R.; Zakaria, Z.; Awang, N.A.; Zalkepali, N.U.H.H.
Highlights: Plasma sputtered platinum is a new alternative of a saturable absorber. The sputtering parameter influence the formation of platinum nanoscale islands. Platinum nanoscale islands influence the nonlinear optical response. The performance of the Q-switched fiber laser depends on the sputtering time. Increasing the sputtering time degrades the overall laser performance. Abstract: In this work, we experimentally demonstrate a study on the influence of the parameters of plasma sputtered platinum (Pt) saturable absorbers (SA) on the performance of Q-switched erbium-doped fiber laser (EDFL). We fabricated a set of five Pt saturable absorbers with different sputtering time ranging from 50 to 400 s. The Pt SAs were fabricated via plasma sputter deposition method and deposited directly on the fiber connector end face. Each SA was characterized in terms of morphology and surface roughness, as well as the linear and nonlinear optical parameters. In our setup, the best performance in terms of bandwidth and pulse duration (7.84 nm and 5.2 µs) was achieved with 50 s of sputtering time. This is the first reported study on controlling the parameters of SA by varying the sputtering time of Pt.